THE ROLE OF TECHNOLOGY FOR IMPROVING LISTENING SKILLS : Rahimjonova Xumora Ziyovuddin qizi - Student of Tashkent state pedagogical university , Rahimjonova Xumora Ziyovuddin qizi (Лучшие интеллектуальные исследования, 2024)
The use of technology in language learning has completely changed the way that education is conducted in the modern day, especially when it comes to improving students' listening abilities. In order to better understand how important technology is to improving listening skills, this article examines a variety of digital tools and platforms as well as how they affect language learners. Teachers may provide students with immersive, individualized, and interactive listening experiences that greatly increase their comprehension and retention by utilizing cutting-edge technologies.